Micro-Nano-Bio Diagnostic System for Food Pathogen Detection Revolutionizes Food Safety Management & Protects Consumers Health - Gogolides, Evangelos; Tserepi, Angeliki; Jobst, Gerhard; Friedt, Jean-Michel; Rabus, David; Dupuy, Bruno; Bilkova, Zuzana; Descroix, Stephanie; Viovy, Jean-Louis; Papadakis, George; Gizeli, Electra (Studies in health technology and informatics, 2016)
The development of integrated, fast and affordable platforms for pathogen detection is an emerging area where a multidisciplinary approach is necessary for designing microsystems employing miniaturized devices; these new technologies promise a significant advancement of the current state of analytical testing leading to improved healthcare. In this work, the development of a lab-on-chip microsystem platform for the genetic analysis of Salmonella in milk samples is presented. The heart of the platform is an acoustic detection biochip, integrated with a microfluidic module. This detection platform is combined with a micro-processor, which, alongside with magnetic beads technology and a DNA micro-amplification module, are responsible for performing sample pre-treatment, bacteria lysis, nucleic acid purification and amplification. Automated, multiscale manipulation of fluids in complex microchannel networks is combined with novel sensing principles developed by some of the partners. This system is expected to have a significant impact in food-pathogen detection by providing for the first time an integrated detection test for Salmonella screening in a very short time. Finally, thanks to the low cost and compact technologies involved, the proposed set-up is expected to provide a competitive analytical platform for direct application in field settings.
Keywords: Animals; Food Microbiology; Lab-On-A-Chip Devices; DNA, Bacterial; potravinářská mikrobiologie; zvířata; mléko; Salmonella; laboratoř na čipu; DNA bakterií; Milk